PENGGUNAAN MEDIA KOMIK MELALUI MODEL PEMBELAJARAN CIRC UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI EKOSISTEM SISWA KELAS VII SMP AL – MAUFI TEMPUREJO - Muhamad Andi setiawan (Pendidikan Biologi,Universitas Islam Jember, 2017)
Development is the main activity of the educational process. Reseaches conducted observations in class VII SMP Al Maufi Tempurejo and obtained data about 65% show the value of student < 70. The reseaches want to know the usec comic media through the model of learning CIRC to improve learning outcomes on ecosystem material. The type of research used is classroom action research (CAR). The procedure used is the cycle model. Based on the results of classical completeness of students in first cycle on 76,6% and the second cyrcle on 91%. While the results of student repetition in first cycle obtained an average of 71,60 and in second cycle of 80,29%. It proves that student learning outcomes can increase with the use of media comic through the learning model CIRC.